1997
DOI: 10.1177/026988119701100211
|View full text |Cite
|
Sign up to set email alerts
|

The frontal lobes and neurosurgery for psychiatric disorders

Abstract: The frontal lobe has been the main target for surgical treatment of mental illness over the last 60 years. Initially the surgery was crude and performed on patients with many different psychiatric disorders. Contemporary surgery utilizes stereotactic lesions which interrupt fronto-thalamic and/or fronto-cingulate fibres. The findings of clinical, neurochemical, neuroimaging, neuropsychological and physiological research in this area are summarized. Current advances in clinical neuroscience methods should be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…An increasing number of studies have identified it as the focus of dysfunction. In support of this hypothesis, a decrease in sACC activity has been reported as part of the clinical response to different antidepressant treatments, including specific serotonin reuptake inhibitors (SSRIs) antidepressant medications, electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), ablative surgery and DBS (Dougherty et al, 2003;Goldapple et al, 2004;Malizia, 1997;Mayberg et al, 2000;Mayberg et al, 2005;Mottaghy et al, 2002;Nobler et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…An increasing number of studies have identified it as the focus of dysfunction. In support of this hypothesis, a decrease in sACC activity has been reported as part of the clinical response to different antidepressant treatments, including specific serotonin reuptake inhibitors (SSRIs) antidepressant medications, electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), ablative surgery and DBS (Dougherty et al, 2003;Goldapple et al, 2004;Malizia, 1997;Mayberg et al, 2000;Mayberg et al, 2005;Mottaghy et al, 2002;Nobler et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, in healthy volunteers, increases in rCBF during sadness (vs. neutral state) have been found in the ventral compartment (subgenual prefrontal cortex, insula, and ventral prefrontal cortex) and rostral compartment (eg, rostral ACC) 6,19,20 , whereas decreased rCBF associated with sad mood has been reported for components of the dorsal compartment (eg, DLPFC, dACC) and inferotemporal cortex 6,19,20 . In depressed patients, pretreatment abnormalities in rCMRglc and rCBF found in prefrontal, and limbic‐paralimbic areas in depressed patients appear to normalize with recovery from depression 6,22–34 . The direction of change from pre‐ to posttreatment often reflects a reversal of the pattern seen with provoked sadness in mood challenge studies in healthy volunteers 6,27–29 .…”
Section: Neuroimaging and The Neurocircuitry Of Mood Disordersmentioning
confidence: 99%
“…Both effective drug treatments and psychotherapy reduce orbitofrontal and basal ganglia over activity in OCD and the fact that neurosurgical interruption of one of these pathways can be therapeutic may confirm its central role (Hay et al, 1993;Malizia, 2000). Nevertheless, the same surgical interventions have been sporadically used in Sweden for panic disorder with good reported effects (Ruck et al, 2003).…”
mentioning
confidence: 99%